Improved academic performance and enhanced employability? The potential double benefit of proactivity for business graduates. Issue 8 (16th November 2016) - Tymon, Alex; Batistic, Sasa
ABSTRACT: This study contributes to proactivity theory and debate on how universities meet competing stakeholder demands in an increasingly marketized higher education environment. We explore how the interplay between the stable facet of proactive personality and the situated behaviour of personal initiative influence academic performance. We hypothesized and found that students high on both these facets of proactivity achieve better academic grades than those low on both, or high in just one. Unexpectedly, high proactive personality with low personal initiative behaviour was the worst combination. Proactivity can be a valuable employability asset, which alongside academic grades is important to some employers as well as students and universities. We argue that nurturing student proactivity can therefore produce multiple benefits but with focus on the more trainable dimension of personal initiative behaviour. To this end we provide practical guidance for university curriculum design to simultaneously enhance graduate employability and academic performance.